Neuroendocrine tumor gall bladder: A case report and review of literature - Aashita; Vikas Yadav; Anuja Kapoor; Rajiv Sharma (Journal of Medical Sciences, 2022)
Neuroendocrine tumor (NET) of gallbladder (GB) is very rare, accounting for 0.5% of all neuroendocrine malignancies and 2% of all GB cancers. It is very difficult to differentiate between carcinoma GB and NET GB. Here, we present a case of NET GB diagnosed in a 40-year-old female. The clinical features were nonspecific and the diagnosis was confirmed only on histopathological examination. The management of carcinoma GB and NET GB is discussed in detail.